Impact of the critical factors of customer experience on well-being: Joy and customer satisfaction as mediators - Xie, Chunchang; Jin, Junxi; Guo, Xiaoling (Frontiers in Psychology, 2022)
This study constructs a formation model of CWB in customer experience with joy and customer satisfaction as mediating factors linking three critical factors – convenience, performance and relationship of customer experience with CWB. By collecting data from customers of retailing, the model was empirically tested. The results show that the three critical factors all have positive effects on CWB. Meanwhile, service performance has a direct effect on CWB. Joy plays a key role in the formation of CWB mediating the relationship between the three critical factors and CWB. This study is the first in the literature to explore CWB from the perspective of customer experience with joy as an antecedent of CWB, and explores the direct effect of service performance on CWB. It provides important implications for managers to enhance customer experience and CWB in the service setting.